How reliable and safe is full-body low-dose radiography (LODOX Statscan) in detecting foreign bodies ingested by adults?. Issue 7 (25th July 2012) - Mantokoudis, Georgios; Hegner, Simone; Dubach, Patrick; Bonel, Harald Marcel; Senn, Pascal; Caversaccio, Marco Domenico; Exadaktylos, Aristomenis K
Abstract : Objective: Foreign body ingestion is common and potentially lethal. This study evaluates the use of low-dose Statscans (LODOX) in emergency departments. Design: This comparative cross-sectional study retrospectively assessed 28 289 digital chest x-rays and 2301 LODOX scans performed between 2006 and 2010 at a tertiary emergency centre. The radiographic appearance, image quality and location of ingested foreign bodies were evaluated in standard digital chest and LODOX radiography. The mean irradiation (μSv) and cumulative mean radiation dose per patient with the ingested foreign body were calculated according to literature-based data, together with the sensitivity and specificity for each modality. Results: A total of 62 foreign bodies were detected in 39 patients, of whom 19 were investigated with LODOX and 20 with conventional digital chest radiography. Thirty-three foreign bodies were located in the two upper abdominal quadrants, 21 in the lower quadrants—which are not visible on conventional digital chest radiography—seven in the oesophagus and one in the bronchial system. The sensitivity and specificity of digital chest radiography were 44.4% and 94.1%, respectively, and for the LODOX Statscan 90% and 100%, respectively. The calculated mean radiation dose for LODOX investigations was 184 μS, compared with 524 μS for digital chest radiography. Conclusions: LODOX Statscan is superior to digital chest radiography in the diagnostic work-up of ingested foreign bodies because it makes it possible to enlarge the field of view to the entire body, has higher sensitivity and specificity, and reduces the radiation dose by 65%.